Well-being and mental health − diet, supplements, exercise or sleep? A review of reports from the last five years - ELŻBIETA GRZYWACZ; ALEKSANDRA JAROŃ (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
In the 2020s we are faced with a problem of an ageing society. Not only do we see it and struggle to provide care for the elderly, but we also focus on constantly maintaining a good form related to our well-being as well as physical, mental and social functioning. The publications used in this review were sourced from the PubMed database and from Google Scholar. The paper uses articles published in English which are not older than 5 years. A‪nalysis of the latest literature has shown that there is evidence that modifiable factors have a positive effect on our well-being and health. The best effect can be achieved by combining positive actions in the field of diet, supplementation, moderate but systematic physical activity, and adding the right amount of sleep per day.